A multi-enzyme microreactor-based online electrochemical system for selective and continuous monitoring of acetylcholine. Issue 11 (22nd December 2014) - Lin, Yuqing; Yu, Ping; Mao, Lanqun
Abstract : This study demonstrates an online electrochemical system (OECS) for selective and continuous measurements of acetylcholine (ACh) through efficiently integrating in vivo microdialysis, a multi-enzyme microreactor and an electrochemical detector. Abstract : This study demonstrates an online electrochemical system (OECS) for selective and continuous measurements of acetylcholine (ACh) through efficiently integrating in vivo microdialysis, a multi-enzyme microreactor and an electrochemical detector. A multi-enzyme microreactor was prepared first by co-immobilizing two kinds of enzymes, i.e. choline oxidase (ChOx) and catalase (Cat), onto magnetite nanoparticles and then confining the as-formed nanoparticles into a fused-silica capillary with the assistance of an external magnet. The multi-enzyme microreactor was settled between an in vivo microdialysis sampling system and an electrochemical detector to suppress the interference from choline toward ACh detection. Selective detection of ACh was accomplished using the electrochemical detector with ACh esterase (AChE) and ChOx as the recognition units for ACh and Prussian blue (PB) as the electrocatalyst for the reduction of hydrogen peroxide (H2 O2 ). The current recorded with the OECS was linear with the concentration of ACh ( I /nA = −3.90 C ACh /μM + 1.21, γ = 0.998) within a concentration range of 5 μM to 100 μM. The detection limit, based on a signal-to-noise ratio of 3, was calculated to be 1 μM. Interference investigation demonstrates that the OECS did not produce an observable current response toward physiological levels of common electroactive species, such as ascorbic acid (AA), dopamine (DA), 3, 4-dihydroxyphenylacetic acid (DOPAC), and uric acid (UA). The high selectivity and the good linearity in combination with the high stability may enable the OECS developed here as a potential system for continuous monitoring of cerebral ACh release in some physiological and pathological processes.